A Genealogy of Radical Librarianship: Collectivity, Action, and Organization as an Alternative to Critical Librarianship - Bowie, Simon; Britton, Siobhán; Sanders, Kevin (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2025)
Radical librarianship and critical librarianship are in some ways complementary approaches to politically-motivated change within librarianship and information science. Despite their similarities, radical librarianship has remained a somewhat fringe position and has not gained the comparatively mainstream acceptance of critical librarianship. Though the history of radical librarianship stretches back to the 1960s and 1970s, it was recently promoted in the United Kingdom and Ireland through Radical Librarians Collective, an organized collective of library worker activists rooted in anarcho-syndicalist and feminist principles that was active between 2013 and 2018. Through outlining a brief history of the Radical Librarians Collective and other radical librarianship movements and groups, we reflect on the differences of approach between radical librarianship and critical librarianship. In particular, we contrast the two approaches’ differing orientation towards political action and how this impacts the dilution and appropriation of critical librarianship work in the political mainstream of librarianship with a specific focus on decolonization work in libraries. We end by considering the limitations and organizational failings of the Radical Librarians Collective as a way to consider possible futures for both radical and critical librarianship. We argue that radical librarianship offers a more practice-based approach than critical librarianship, emphasising political activism, direct action, and the building of local radical alternatives in a way that could offer a dialectical unity with critical librarianship.